FIQH MUAMALAH DALAM TATA KELOLA DANA PUBLIK: STUDI KASUS FILM MERAH PUTIH ONE FOR ALL - Asih Pertiwi; Agustinar; Dimas Muhammad Hanief Arkaan; Dessy Asnita; Yaser Amri (Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2026)
The animated film project Merah Putih: One For All has attracted widespread public criticism due to the perceived mismatch between the substantial public funding allocated and the quality of its output. Beyond concerns over budget efficiency, the controversy reflects a broader crisis of public trust regarding transparency, accountability, and legitimacy in the management of public funds within the national creative industry. Existing studies generally examine public accountability or creative industry governance separately, whereas this study offers a novel perspective by integrating fiqh muamalah principles with maqashid sharia, particularly the principle of hifz al-mal (protection of wealth), to evaluate public fund management in a state-supported creative project. This study aims to analyze the governance of public funds from the perspective of fiqh muamalah and examine its implications for public trust. A descriptive qualitative approach was employed through document analysis of official reports, news articles, and public discourse on social media, supported by the concepts of amanah, maslahah, and accountability in Islamic public finance. The findings reveal that the project demonstrates inconsistencies between public expenditure and measurable public benefit, indicating shortcomings in the implementation of amanah and maslahah. These shortcomings have contributed to declining public trust and intensified demands for greater transparency and performance-based evaluation of publicly funded creative initiatives. This study contributes to the literature by proposing fiqh muamalah as an ethical-analytical framework for assessing accountability in public fund management within the creative industry, thereby extending the application of Islamic economic principles beyond conventional public finance studies. Keywords: fiqh muamalah, public funds, creative industry, maqashid sharia, public trust